Computational Investigation on Series of Metal‐Free Sensitizers in Tetrahydroquinoline with Different π‐spacer Groups for DSSCs. Issue 14 (10th April 2019) - Arunkumar, A.; Deepana, M.; Shanavas, S.; Acevedo, R.; Anbarasan, P. M.
Abstract: Dye‐sensitized solar cells (DSSCs) have considerable attention to the academic and industrial community. Because, it makes solar energy efficient and cost effective to harness. DSSCs is one of the important roles in the design of sensitizers with sustainable and environmentally‐friendly materials. In the present work, a series of D‐π‐A architecture with tetrahydroquinoline based organic dye sensitizer were designed and modifying π‐linker (SP1‐SP9) for the potential use in DSSCs application by DFT and TD‐DFT calculations. There are different functional groups were analyzed through a proper methodology for calculations and comparison with C1‐1 dye. From these functionals, the TD‐ωB97XD method was reasonably capable of predicting the absorption spectra of the molecules. Moreover, SP1‐SP9 dye molecules were systematically analyzed by using various parameters such as the energy gap ( E g ), absorption spectra, light harvesting efficiency ( LHE ), open circuit photovoltage ( e V O C ), dipole moment ( μ n o r m a l ), free energy change for electron injection ( Δ G i n j e c t ), regeneration ( Δ G r e g ) and chemical hardness ( η ). As a whole, all the designed dyes, especially SP6, SP7, SP8 dyes are showed smaller E g, red‐shift absorption spectra, largest μ n o r m a l, negative Δ G i n j e c t and fastest Δ G r e g values, compared to C1‐1. Based on our result shows that SP6, SP7 and SP8 dye molecules are the best candidates to provide superior performances in the DSSCs application. Abstract : A series of D‐π‐A design with tetrahydroquinoline based dye sensitizers designed and modified (SP1‐SP9) for the potential use in DSSCs by DFT and TD‐DFT calculations were successfully. TD‐ωB97XD functional was reasonably capable of predicted the UV‐Vis absorption spectra of the SP1‐SP9 dye molecules. TD‐DFT method displays that lower energy gap values of SP6, SP7 and SP8 were demonstrated broader UV‐Vis spectrum. Particularly, SP6, SP7 and SP8 dyes are the best applicants to deliver superior acts in the DSSCs.